2012
DOI: 10.1097/ogx.0b013e318247c7f9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Type II Diabetes and Metformin Use to Ovarian Cancer Progression, Survival, and Chemosensitivity

Abstract: OBJECTIVE-To estimate whether metformin use by ovarian cancer patients with type II diabetes was associated with improved survival. METHODS-We reviewed the effect of diabetes and diabetes medications on ovarian cancer treatment and outcomes in a single-institution retrospective cohort. Inclusion criteria were International Federation of Gynecology and Obstetrics (FIGO) stage I-IV epithelial ovarian, fallopian or peritoneal cancer. Exclusion criteria were noninvasive pathology or non-epithelial malignancies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…A retrospective case note review of patients with breast cancer receiving neoadjuvant chemotherapy (67) demonstrated a remarkable 24% complete pathologic response (cPR) in diabetic patients incidentally taking metformin and receiving neoadjuvant chemotherapy compared with 16% cPR in nondiabetics and 8% cPR in diabetics not receiving metformin. A similar, also historical, series of epithelial ovarian cancer has demonstrated clinical benefit with increased progression-free survival and overall survival in diabetics taking metformin and receiving taxane/carboplatin chemotherapy compared with nondiabetics or diabetics not on metformin (68). However, incidental metformin use has not demonstrated survival benefit in two case series of diabetics with breast cancer (5,67).…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 98%
“…A retrospective case note review of patients with breast cancer receiving neoadjuvant chemotherapy (67) demonstrated a remarkable 24% complete pathologic response (cPR) in diabetic patients incidentally taking metformin and receiving neoadjuvant chemotherapy compared with 16% cPR in nondiabetics and 8% cPR in diabetics not receiving metformin. A similar, also historical, series of epithelial ovarian cancer has demonstrated clinical benefit with increased progression-free survival and overall survival in diabetics taking metformin and receiving taxane/carboplatin chemotherapy compared with nondiabetics or diabetics not on metformin (68). However, incidental metformin use has not demonstrated survival benefit in two case series of diabetics with breast cancer (5,67).…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 98%
“…27 However, reports are now starting to show that patients with ovarian cancer with type 2 diabetes who used metformin had longer progression-free survival after surgery and chemotherapy, despite receiving similar treatment. In a single-center study by Romero and colleagues, 27 341 patients with ovarian cancer were evaluated, of which 297 did not have diabetes, 28 had type 2 diabetes and did not use metformin, while 16 type 2 diabetic patients were taking metformin. The authors reported that 5-year progression-free survival for patients undergoing the same chemotherapy treatment was 51% for diabetic patients who used metformin, in comparison to 23% for the nondiabetic patients and 8% for the diabetic patients who did not use metformin.…”
Section: Discussionmentioning
confidence: 99%
“…[101][102][103][104][105][106][107][108][109] The inconsistent findings across studies may be due to their retrospective design, inappropriate comparators or the use of exposure data from sources such as medical records and automated pharmacy databases.…”
Section: Cancer Outcomesmentioning
confidence: 98%